REPRESENTATION OF GESTALTS IN DIFFERENT SYNONYMIC DICTIONARIES AND CONTEXTS (Scientific journal of the Fergana State University, 2024)
This article, the synonyms characteristic of language universals are analyzed in the cognitive paradigm. Cognitive linguistics, which is considered a part of linguistics, involves looking at events as a whole or as part of an event in the development of concepts. The idea that the gestalt structure of the concept corresponds to the structure of its associative field is of particular importance in the article. Therefore, synonyms are one of the linguistic means of representation of associative relations, in which the results of the formation of the corresponding gestalt and the analysis based on dictionaries are given because the boundary of the synonymous line is open.